The effect of extending the duration of eligibility in an Italian labour market programme for dismissed workers - Enrico Rettore; Adriano Paggiaro; Ugo Trivellato (Institute for the Study of Labor (IZA), 2008)
Liste di mobilità (LM) is an Italian labour market programme targeted to dismissed workers. It combines a 'passive' component granting monetary benefits to employees dismissed by firms larger than 15 employees, and an 'active' component providing an employment subsidy to any firm hiring workers from the LM. Eligibility duration varies with the worker's age at dismissal. Using a new linked administrative panel data set for an Italian region, we exploit the variability of these provisions to evaluate the impact of extending the duration of eligibility on re-employment probabilities and wages over the 36 months subsequent to enrolment in the programme. The average treatment effect is identified via a Regression Discontinuity Design. We validate the design by a set of overidentification tests. For most of the sub-groups we analyse, we find that a longer eligibility period has no impact on re-employment rates. A negative impact emerges for women entitled to monetary benefits at the end of the second year of eligibility, but it disappears one year later. A major negative impact emerges for workers aged 50 or more granted the monetary benefits; it is most likely due to the fact that they can use the LM as a bridge to retirement.
urn:nbn:de:101:1-20080820188
Keywords: C31; 330; Active labour market policies; regression discontinuity design; Arbeitsmarktpolitik; Arbeitslosenversicherung; Lohnsubvention; Dauer; Altersgruppe; Wirkungsanalyse; Berufliche Integration; Italien